Understanding the High Ionic Conductivity in Nanostructured Ytterbium Stabilized Zirconia Thin Films. (1st October 2015) - Benítez-Rico, A.; García-Sánchez, M. F.; Picquart, M.; Monroy-Peláez, B. M.; Santana-Rodríguez, G.
Abstract : Recently, high ionic conduction has been reported in nanostructured materials. This increase in conductivity can be important in technological applications, including micro-Solid Oxide Fuel Cells, so the understanding of this phenomenon is essential. In this work, XRD, Raman spectroscopy, SEM, EDS maps, and UV-Visible spectroscopy measurements are used to have an insight into the relationship between structural and electrical properties in nanostructured ytterbium stabilized zirconia (YbSZ) thin films prepared by ultrasonic spray pyrolysis. Raman measurements allowed the identification of a mixture of tetragonal and cubic phases at 4% of Yb doping, which cannot be detected by XRD, while the compositional maps suggest that Yb can be located preferentially in the grain boundaries. Changes in the activation energy values in bulk and grain boundaries are related to the small grain sizes (≤10 nm). UV measurements support the ionic nature of the charge transport. These results indicate that the high conductivity is a consequence of different physical parameters in the films such as stress in the materials, different crystalline phases, impurities diffusion to the grain boundaries, and the presence or absence of electronic conduction. A model that explains the increase of conductivity in nanostructured materials must include all these aspects.